Nilai-nilai Pendidikan Jiwa dalam Buku Tasawuf Modern Karya Buya Hamka - Nurhadi Nurhadi; Fahrul Rozi (LP2M STIT Palapa Nusantara, 2020)
Soul education is the process of growth, maintenance, and education of what is called the soul as a totality of people with good and bad potential. The soul is the basic substance of man to produce thoughts, behaviors, actions, and perspectives, which can be positive or negative. This study aims to reveal the values ​​of mental education according to Buya Hamka. This research is a library research with a content analysis approach. The source of the data was obtained through Buya Hamka's book titled Modern Tasawuf published by Panjaka Panjimas Library, Jakarta in 1990. The research found that in the modern Sufism book by Buya Hamka there were values ​​of mental education, among others; 1) Associating with wise people; 2) Getting used to thinking work; 3) Maintain lust and anger; 4) Tadbir, weigh before working (work regularly); 5) Investigate the defects (disgrace) yourself; 6) Angry; 7) Ujub; 8) Arguing and breaking friends' words 9) Senda banter and banter; 10) Zuhud; 11) Fair; 12) Fear of death; 13) Upside down promises and grudges.